2017
DOI: 10.1016/j.rser.2016.08.024
|View full text |Cite
|
Sign up to set email alerts
|

A pressure-based method for monitoring leaks in a pipe distribution system: A Review

Abstract: Leakage from a pipe network possibly poses significant environmental destruction and economic losses due to the release of potential energy. While the pipe network may be planned and constructed to satisfy the requirements of rigorous conditions, it is quite hard to avoid the subsequent appearance of leakages in a pipeline during the system's lifetime. Pressure leak detection enables a fast and reliable action response which is necessary to minimise the damage. Many leak detection approaches have been previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(54 citation statements)
references
References 29 publications
0
49
0
5
Order By: Relevance
“…e characteristic line grid is shown in Figure 1. Equations (9) and (11) are C+ and C− characteristic lines AP and BP, respectively; equations (8) and 10are the compatibility equations for satisfying the respective characteristic lines. e pipes are equally divided into N equal parts, the step size is Δx, and the time step is Δt � aΔx.…”
Section: Governing Equation Gas Continuity and Equation Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…e characteristic line grid is shown in Figure 1. Equations (9) and (11) are C+ and C− characteristic lines AP and BP, respectively; equations (8) and 10are the compatibility equations for satisfying the respective characteristic lines. e pipes are equally divided into N equal parts, the step size is Δx, and the time step is Δt � aΔx.…”
Section: Governing Equation Gas Continuity and Equation Of Motionmentioning
confidence: 99%
“…In 2017, Abdulshaheed proved that the biggest problem in the use of the inverse transient method is that the modeling of transients in the system does not accurately reflect the actual situation, and the calculated data and measured experimental data are very different. e difference is mainly because the model does not accurately consider the multidimensional effect of unstable friction [11]. In 2017, Chen et al tested the transient model of pipeline leakage through the characteristic line method and confirmed that the positioning results calculated using the starting and ending pressure and flow results at the steady state after pipeline leakage are close to the real values [12].…”
Section: Introductionmentioning
confidence: 99%
“…An air blower with a hollow blade and a special transmission system was designed to press the air into the leakage gap, which offset the leakage caused by the side pressure and suction in the axial fan. Abdulshaheed et al 17 analysed a variety of leakage testing methods under pressure and discussed the leakage problems in stable and unstable states and summarized different detection methods for special oil and water conveyance purposes. Abdulshaheed et al 17 analysed a variety of leakage testing methods under pressure and discussed the leakage problems in stable and unstable states and summarized different detection methods for special oil and water conveyance purposes.…”
Section: Introductionmentioning
confidence: 99%
“…During the analysis of the leakage, Fox et al 16 especially considered the interaction between structure and leakage dynamics then proposed a throttle equation with constant flow coefficient to use and accurately estimate the dynamic leakage flow of longitudinal cracks. Abdulshaheed et al 17 analysed a variety of leakage testing methods under pressure and discussed the leakage problems in stable and unstable states and summarized different detection methods for special oil and water conveyance purposes. Eparu et al 18 used a numerical simulation of gas leakage in buried pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-parameter dynamical measurement of hydraulic piping systems is needed for performance testing and real-time condition monitoring to prevent fatigue failure [6][7][8][9]. State-of-the-art multi-parameter dynamical measuring technology and systems with high accuracy, good environmental adaptability and low cost, and permitting easy integration and operation, are in high demand [10,11]. However, traditional electrical/piezoelectric sensors (such as resistance strain gauges, thermocouples, piezoelectric accelerometers, and electric pressure transducers) and electronic instruments, and non-destructive evaluation methods (for example, ultrasonic, acoustic emission, radiography, magnetic particle, and magnetic flux), are not suited to harsh environments [12,13].…”
Section: Introductionmentioning
confidence: 99%